Analisis Putusan Hakim Dalam Gugatan Wanprestasi Perjanjian Utang Piutang Modal Usaha - Azzahra, Viola Farica; Ivanicevic, Johan; Huda, Genthala Rafik; Sianturi, Catherine Rosalina; Simanjuntak, Cristella Zevanya Rhadot; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
This study discusses the Analysis of Decision Number 1245/Pdt.G/2023/PN.Sby, highlighting cases of default where the defendant failed to fulfill its achievements as agreed in the agreement. In the context of civil law, this default is a deviation from the obligations agreed upon by both parties. In this case study, the method used is the normative juridical method, which uses a legal perspective based on applicable legal regulations. The Panel of Judges had considerations that supported rejecting the plaintiff's claim. From a civil law perspective, the rejection of this lawsuit shows that in cases of breach of contract, it is important for the plaintiff to formulate the lawsuit clearly and in accordance with the facts presented, as well as ensuring that the petitum requested is consistent with the posita submitted.